2018
DOI: 10.1007/s00284-018-1532-y
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans in Umbilical Cord Blood, Peripheral Blood, and Saliva from Healthy Mothers

Abstract: The aims of this study were to analyze the presence of Streptococcus mutans (SM)-DNA in cord blood (CB), maternal peripheral blood (PB), and maternal saliva (SA) and compare with data collected in health surveys. Sixty-four healthy women with pregnancies to term and without complications attending for elective cesarean section in the Clinical Hospital of Ribeirao Preto, Sao Paulo were included. Samples of PB and unstimulated SA were obtained on the day of hospitalization and samples of CB were collected after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Riggs et al found that the hematogenous spread of Mycoplasma pulmonis to the rat fetus can occur without amniotic fluid infection and indicated that the fetus itself can spread the amniotic fluid with microbes 18 . Mendes et al found that Streptococcus mutans could migrate from saliva to maternal peripheral blood and cord blood and that tooth brushing increased S. mutans detection in blood samples 19 . However, the mechanism by which oral microbial species move from gravidae to the fetus is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Riggs et al found that the hematogenous spread of Mycoplasma pulmonis to the rat fetus can occur without amniotic fluid infection and indicated that the fetus itself can spread the amniotic fluid with microbes 18 . Mendes et al found that Streptococcus mutans could migrate from saliva to maternal peripheral blood and cord blood and that tooth brushing increased S. mutans detection in blood samples 19 . However, the mechanism by which oral microbial species move from gravidae to the fetus is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%